PENERAPAN MODEL PHENOMENON BASED LEARNING (PHENOBL) PADA MATERI SUHU DAN KALOR UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISWA KELAS XI SMA - Azmi, Said Nurul; Irawan, Dedi; Azhar, Azhar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract : Learning physics in its application is not just gathering knowledge, but must emphasize giving direct experience to foster the ability to think, work and act scientifically and communicate it as an important aspect of life skills. Therefore, to facilitate the learning process of physics must use creative and innovative ways so that learning objectives can be achieved optimally. The results of the 2015 Trends in International Mathematics and Science Study (TIMSS) state that students' understanding of concepts in learning physics is still very low, therefore to improve students' conceptual understanding in the 21st century, an alternative can be done through the application of the PhenoBL learning model so that the learning process learning becomes interesting and fun for students in understanding and relaxed. This study aims to describe and find out the differences in students' understanding of concepts that apply the Phenomenon Based Learning model with conventional learning. The type of research used was a Quasi Experiment with a Posttest Only Design, namely using one experimental class and one control class. The sampling technique used is simple random sampling. The sample in this study were students of SMAN 1 Mandah with class XI IPA 2 as the experimental class and class XI IPA 1 as the control class. The research data was collected by giving a test in the form of a posttest which totaled 14 questions which were analyzed descriptively and to see an increase in students' conceptual understanding using SPSS 23 as an inferential analysis. The results of the research from the descriptive and inferential analysis showed that the students' understanding of the concepts in the experimental class and the control class were different, especially in terms of temperature and heat, the average score of the experimental class was higher than that of the control class. From this study it can be concluded that the PhenoBL model can improve students' understanding of concepts at SMAN 1 Mandah.Keywords: Concept Mastery, PhenoBL model, temperature and heat .